INDUSTRIALISASI TRADISI SHALAWATAN, DARI DAKWAH MENUJU KOMODITAS - Fuad, Mohammad Zuhurul (Islamic Studies Journal for Social Transformation, 2024)
This research aims to look at the phenomenon of reading prayers in the Az-Zahir prayer group. Shalawat, which previously had the value of worship, is slowly turning into an activity that has the value of profit. The main question in this research is "How is prayer commodified in the Az-Zahir Shalawat Group?". This research is qualitative type with a netnographic approach. Data is collected through documentation of scientific work and content related to the research theme. Data analysis uses Miles and Huberman content analysis techniques. The results of this research show that the commodification of prayer in the Az-Zahir group is viewed through three aspects. content commodification, audience commodification, and worker commodification.